Porocarcinoma of the Groin: A Case Report - Hannah E. Myers; Keith Pennycook; Joshua Hammel (Karger Publishers, 2024)
Introduction: Porocarcinoma is a rare skin cancer that arises from the intraepidermal ducts of sweat glands. It is classically found in the 60-70-year-old age group, and lesions are most commonly reported on the head and neck or lower extremities. Case Presentation: This case focuses on a 49-year-old man who presented to an outpatient dermatology clinic with a growing, painful nodule in his right groin. A shave biopsy was conducted and resulted in a diagnosis of a porocarcinoma. Conclusion: Porocarcinoma is an extremely rare skin cancer that most commonly occurs on the head, neck, or lower extremities of 60-70-year-olds. This report details the interesting findings of a porocarcinoma in an unexpected location and age group and reviews pertinent literature.